Heterophyton, a new substitute name for Allophyton X.W. Wu (Pteridopsida) - Wang, Faguo; Xing, Fuwu (Phytotaxa, 2014)
The filicopsid pteridophyta genus Allophyton X.W. Wu (1982) was established for A. dengqenensis X.W. Wu collected in Badasongduo, Dingqing County of Xizang Province, China. It was listed in Index of generic names founded on Mesozoic-cenozoic specimens from China (Wu 1993: 498) and its taxonomic position is unsettled. Rhizomopteris Schimp. (1869: 699) differs from it in its fine and furcate stem, and bundle scar in leaf scar hippocrepiform, Caulopteris Lindl. & Hutton (1832: xlix) differs from it in its leaf scar regular spread, and bundle scar in leaf scar hippocrepiform. The materials of Allophyton were collected in Mesozoic Coal Series strata, coal-bearing strata that were regarded as Jurassic by Li (1955) and from late Triassic to early-middle Jurassic by Si & Zhou (1962).